Quinoline- and Isoindoline-Integrated Polycyclic Compounds as Antioxidant, and Antidiabetic Agents Targeting the Dual Inhibition of α-Glycosidase and α-Amylase Enzymes - Mohammed Al-Ghorbani; Osama Alharbi; Abdel-Ba; Naaser A. Y. Abduh (MDPI AG, 2023)
Novel analogs of quinoline and isoindoline containing various heterocycles, such as tetrazole, triazole, pyrazole, and pyridine, were synthesized and characterized using FT-IR, NMR, and mass spectroscopy, and their antioxidant and antidiabetic activities were investigated. The previously synthesized compound 1 was utilized in conjugation with ketone-bearing tetrazole and isoindoline-1,3-dione to synthesize Schiff's bases 2 and 3. Furthermore, hydrazide 1 was treated with aryledines to provide pyrazoles 4a-c. Compound 5 was obtained by treating 1 with potassium thiocyanate, which was then cyclized in a basic solution to afford triazole 6. On the other hand, pyridine derivatives 7a-d and 8a-d were synthesized using 2-(4-acetylphenyl)isoindoline-1,3-dione via a one-pot condensation reaction with aryl aldehydes and active methylene compounds. From the antioxidant and antidiabetic studies, compound 7d showed significant antioxidant activity with an EC50 = 0.65, 0.52, and 0.93 mM in the free radical scavenging assays (DPPH, ABTS, and superoxide anion radicals). It also displayed noteworthy inhibitory activity against both enzymes α-glycosidase (IC50: 0.07 mM) and α-amylase (0.21 mM) compared to acarbose (0.09 mM α-glycosidase and 0.25 mM for α-amylase), and higher than in the other compounds. During in silico assays, compound 7d exhibited favorable binding affinities towards both α-glycosidase (−10.9 kcal/mol) and α-amylase (−9.0 kcal/mol) compared to acarbose (−8.6 kcal/mol for α-glycosidase and −6.0 kcal/mol for α-amylase). The stability of 7d was demonstrated by molecular dynamics simulations and estimations of the binding free energy throughout the simulation session (100 ns).